Contesting the Independence of Village Head Election Organizers with E-voting - Tjahjoko, Guno Tri (Journal of Governance and Public Policy, 2022)
This article describes the intervention of the Sleman local government in village administration, especially in implementing the e-voting village head election. The argument of the Sleman local government is that the e-voting device for the election of the village head is smart, fast, and accurate. The author rejects this argument, because of the involvement of 59 state civil servants as the main technical team. The involvement of ASN in the election of e-voting village heads indicates that the independence of the organizers is lost. The involvement of ASN in the election of lurah has violated Law No. 16/2014, article 32. This research method uses an exploratory qualitative approach combined with governmentality. Primary data collection was done through interviews and observations. Secondary data was collected through mapping journals and books. After the data is collected, validation checks are carried out with the principle of triangulation. Data analysis was carried out by combining theory and field data. The results of the study indicate that there are non-independent ASNs that can create a pseudo-legitimacy for the results of the lurah election.